Implementasi Pembelajaran Berbasis Lesson Study Terhadap Kompetensi Pedagogik dan Keterampilan Proses Sains Guru Biologi SMA Negeri 11 dan MA Negeri 3 Kota Banda Aceh - Eva Murtisal; Cut Nurmaliah; Safrida Safrida (Biotik, 2016)
The study entitled â€œThe Implementation of the Lesson Study Based Learning toward the Teachersâ€™ Pedagogical Competence and Science Process Skill of Biology Teachersâ€™ at SMA Negeri 11 and MA Negeri 3 Banda Acehâ€. It aimed to describe the teachersâ€™ pedagogical competence and Science Process Skill of Biology teachers at SMA Negeri through lesson study focusing on the product learning instruments. The data analysis the pedagogical and science process skill was using descriptive percentage in qualitative. The study result of the pedagogical competence of biology teachersâ€™ through the lesson study atSMA Negeri 11 and MA 3 Banda Aceh were running well in which the value of pedagogical competence at SMA Negeri 11 was 99% (very good category) and MA Negeri 3 Banda Aceh was 92% (good category). The teachersâ€™ science process skill overall was very good category, with the score 72 for model teacher at SMA 11 Banda Aceh and 67 for model teacher at MAN 3 Banda Aceh.